Novel coumarin chalcone derivatives: synthesis, docking, and antimicrobial evaluation - Kumari, Sumita; Sharma, Amit; Yadav, Sonia (Journal of Applied Pharmaceutical Research, 2025)
Background: This study synthesized and evaluated a series of coumarin chalcones for their antimicrobial efficacy against microbial and fungal strains. Methodology: Ten new coumarin chalcones were prepared by Claisen- Schmidt condensation by using 4-hydroxy coumarin as a precursor and followed by refluxing obtained intermediate (3-(4-aminophenyl)-3-oxo prop-1-enyl)-4-hydroxy-2H-chromen-one) with substituted aromatic benzaldehyde in the presence of piperidine as a catalyst. IR, 1HNMR, 13CNMR, and GCMS characterized all synthesized compounds. The agar well diffusion method assessed these compounds for antimicrobial activity against various bacterial and fungal strains such as E. coli, P. aeruginosa, B. subtills, S. aureus, and C. albicans. Zone inhibition was measured for each compound (10µL) against all strains. Results and Discussion: The study showed that derivatives 4c, 4e, 4f, and 4g showed strong potential for inhibition towards various fungal and microbial strains. The inhibition zone for 4c and 4e was emerged as 5.48±0.448, 7.02±0.332, 5.62±0.321, 6.81±0.021, 7.72±0.421 and 5.13±0.179, 6.76±0.511, 4.24±0.273, 4.64±0.231, 5.48±0.049 while compound 4f and 4g showed 5.40±0.420, 6.69±0.168, 5.71±0.245, 5.28±0.042, 7.09±0.175, and 4.94±0.814, 6.58±.0160, 6.01±0.455, 6.61±0.021, 6.91±0.414 mm, respectively. Between -7.1 to -10.2Kcal/mol is the range of docking score of derivatives by interactions of DNA gyrase and compounds analyzed. Here, compound 4g exhibited the highest DNA gyrase inhibition, and compound 4c exhibited a strong inhibition with docking scores of -10.2 kcal/mol and -9.8 kcal/mol, respectively. Conclusion: The findings of this work contribute to a better understanding the potential of synthesised compounds as drug candidate against microbial infections through ADMET study.